Vocabulary learning strategies among undergraduate ESL learners in tertiary education / Zarinatun Ilyani Abdul Rahman and Nur Farhana Nasri - Abdul Rahman, Zarinatun Ilyani; Nasri, Nur Farhana (Universiti Teknologi MARA, 2020)
Vocabulary learning strategies (VLSs) play a significant role in assisting language learners in the development of language learning. A quantitative study was conducted to explore VLSs employed by undergraduate ESL learners in a public university. Data were collected from a group of 197 ESL learners from three faculties-Accountancy, Applied Science, and Computer and Mathematical Science-in the university. An adopted VLSs questionnaire by Gu & Johnson (1996) was used to answer two research questions: (1) to find the most and least preferred strategies and 2) to identify if there is any significant difference between the ESL learners in three different faculties-Accountancy, Applied Science, and Computer and Mathematical Science - in terms of their vocabulary learning strategies preference. The results were gathered using descriptive analysis and one-way ANOVA followed by a post-hoc test. The results of the study revealed that note taking, memory and guessing using linguistic clues were the three most preferred strategies while guessing using background knowledge and activation were the least preferred ones. In addition, the data also unveiled that there was a significant difference between Accountancy students and Applied Science students as well as Computer and Mathematical Science students both in guessing strategies. It is hoped that the findings of this study can shed some light to the teaching and learning process whereby the educators could employ the best VLSs to assist students in vocabulary learning while learners could be aware of strategies that suit them best.